2021
DOI: 10.3390/ijerph182312388
|View full text |Cite
|
Sign up to set email alerts
|

Will Smog Cause Mental Health Problems? Indication from a Microsurvey of 35 Major Cities in China

Abstract: Using the survey data of 21,861 participants from 35 major cities in China in 2018 and 2019, the effect of air quality on participants’ mental health was empirically tested based on the ordered probit model. The results showed that smog can significantly influence the mental health of participants. The better the air quality, the better the participants’ mental health, while poor air quality results in poor mental health. The older and higher-paid participants demonstrated poorer mental health. Additionally, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Smog not only affects physical health but also has implications for mental health. A Chinese study found that smog adversely affects mental health [7]. Several factors moderate smog's effects on physical health, including age, underlying health conditions, and socioeconomic status.…”
Section: Dear Editormentioning
confidence: 99%
“…Smog not only affects physical health but also has implications for mental health. A Chinese study found that smog adversely affects mental health [7]. Several factors moderate smog's effects on physical health, including age, underlying health conditions, and socioeconomic status.…”
Section: Dear Editormentioning
confidence: 99%